Histopathological study of round cell tumors of the head and neck region in a tertiary care hospital: A retrospective study (Journal of Pathology of Nepal, 2022)
Background: Small round cell tumors are heterogeneous, highly aggressive malignant tumors occuring in unusual sites with overlapping clinical and radiographic features.  Their diagnosis is challenging using conventional histopathologic approaches because of indistinct features in small biopsy samples and hence immunohistochemistry is a must. This study was undertaken to evaluate the pattern, common types, age, sex distribution of round cell tumors of the head and neck region and to obtain morphological immunohistochemistry correlation.Material and Methods: It is a retrospective study of 99 cases which fulfilled the inclusion criteria. Paraffin blocks were retrieved and were reviewed by two independent expert observers and immunohistochemistry was repeated whenever necessary.Results: Final diagnosis was given based on the immunohistochemistry pattern and our study showed 8 spectrums of round cell tumours. Lymphoma was the most common followed by neuroendocrine carcinoma. Most B-cell Non Hodgkin Lymphoma, undifferentiated carcinomas and Neuroendocrine carcinomas were observed in older group whereas, Ewing sarcoma /Primitive Neuro Ectodermal Tumour and T cell NHL were seen more in younger group. According to sex wise distribution, 70 (70.7%) cases were male and 29 (29.3%) females with male to female ratio of 2.4:1.Conclusions: Round cell tumors can occur at any sites of the head and neck region. There are certain morphologic features for each tumor which may help the surgical pathologist to come to a probable diagnosis in addition to careful search of the detailed history, location of tumor, presentation, radiological findings and ultimately correlating with immunohistochemistry.